Simulation-Based Power Estimation for High Throughput SHA-256 Design on Unfolding Transformation - Shamsiah, Suhaili; Norhuzaimin, Julai; Asrani, Lit; Maimun Binti, Huja Hussin; Mohamad Faizrizwan bin, Mohd Sabri (2022)
In recent years, security has grown in importance as a research topic. Several cryptographic SHA-256 hash algorithms have been developed to enhance the performance of data-protection techniques. In security system designs where data transmission must be properly encrypted to avoid eavesdropping and unwanted monitoring, the Hash Function is vital. In constructing the SHA-256 algorithm, high speed, compact size, and low power consumption are all factors to be taken into account for an efficient implementation. The purpose of this project is to reduce dynamic thermal power dissipation of SHA-256 unfolding transformation. State encoding is a method used in reducing power design strategies that have been proposed to lower the dynamic power dissipation of the algorithm. The algorithms are successfully designed using the Altera Quartus II platform. The ModelSim is used to test how accurate the results of simulations written in Verilog code are and to validate them. This study presents the unfolding transformation with Gray encoding approach to reduce the SHA-256 design's power consumption and increase its throughput. The SHA-256 unfolding transformation reduces the amount of clock cycles required for conventional architecture. In this research, the dynamic power SHA-256 unfolding factor 4 with Gray encoding reduces by 43.4 percent from Binary encoding with high throughput of the design. Therefore, it was suggested that to provide high performance of the embedded security system design, an unfolding transformation with Gray encoding design can be applied to the hash function design. Thus, the performance of the SHA-256 design can be greatly enhanced by changing the state encoding with the high number of unfolding factors. Based on this technology, the Power Analyzer in Altera Quartus II may produce an accurate simulation-based power assessment.